Cultivo in vitro de ovócitos bovinos utilizando nanopartículas e levitação magnética - Miglio, Luisa (2019)
The use of the bovine species as an animal model of study is of great importance for Brazilian and world livestock production and even for human assisted reproduction. The maturation of bovine oocytes consists of nuclear and cytoplasmic maturation events, essential for fertilization and for early embryonic development. The present work aims to evaluate the effects of the use of nanoparticles associated with magnetic levitation for three - dimensional culture in the process of in vitro bovine oocyte maturation. One thousand two hundred and fifty-eight oocytes of good and poor qualities were selected and incubated with and without nanoparticles and exposed to a magnetic drive during the maturation period. The process of in vitro fertilization and in vitro cultivation occurred in a traditional way. The evaluations were performed with the help of confocal microscopy (cell death; production of reactive oxygen species (ROS) and dispersion of actin filaments) and transmission electronics (areas occupied by mitochondria; vacuoles; cortical granules and dispersion of microvilli in the perivitelinic space). It was possible to observe that the use of nanoparticles favored the cleavage of low quality oocytes with higher concentration of nanoparticles, but the high concentration of nanoparticles resulted in increased ROS production, reduction in mitochondrial areas and increase in the area occupied by vacuoles. Thus, the use of nanoparticles, despite having a beneficial effect on the cleavage of low quality oocytes, did not have a beneficial effect on the cytoplasmic maturation of oocytes.